Analysis of Radical Feminism in Hagar and The One Who Sees Film Using John Fiske’s Semiotic Approach: - Shabrina Salsabila; Tamim Mulloh (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
With the development of modern social life, the issue of gender equality has become a topic of increasing concern because various forms of injustice are still commonly found in daily life. This study aims to identify and analyze the representation of radical feminist values in the film Hagar and the One Who Sees using John Fiske’s semiotic approach. This research employs a descriptive qualitative approach. The primary data were taken directly from the film Hagar and The One Who Sees, while the secondary data consist of journals, research articles, and literature related to semiotics and feminism. Data collection techniques included watching, taking notes, as well as conducting a literature review and analysis. Data validation was carried out through increased researcher diligence and peer discussion. Data analysis followed the Miles and Huberman model, the stages of data condensation, data presentation, and conclusion drawing. Analysis at the level of reality reveals that facial expressions, simple and worn-out clothing, the barren desert environment, acts of running and refusal, and Hagar’s dialogues reflect suffering and oppression within a patriarchal structure. At the level of representation, cinematographic techniques (long shots, low angles, close-ups, and tracking shots), the use of lighting (low-key vs. natural), and sound or music emphasize Hagar’s alienation, her struggle, and her hope for liberation. At the ideological level, the film represents radical feminist values through its critique of patriarchy. Hagar and The One Who Sees effectively conveys the ideology of radical feminism through its visual and narrative codes, which critique patriarchy and highlight the struggle of women to gain freedom. This study recommends that John Fiske’s semiotic analysis be applied more widely in research on short films and other media that portray issues of gender and oppression, particularly within Middle Eastern cultural contexts..